2019
DOI: 10.1016/j.ijhydene.2019.10.095
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical study of the insertion and diffusivity of hydrogen in the Ti3Al-D019 system: Comparison with Ti-hcp and TiAl-L10 systems

Abstract: Using first-principles calculations, the insertion and diffusivity of hydrogen in the Ti 3 Al-D0 19 system are presented and discussed. After a brief description of the properties of Ti 3 Al, the different sites of insertion are identified and discussed. The octahedral configuration surrounded by Ti atoms only (2a Wyckoff position) is found to be the preferred insertion site for H atoms. The second octahedral and the two tetrahedral sites are found significantly less stable than 2a sites. Phonon, electronic an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 51 publications
1
2
0
Order By: Relevance
“…They could show that all these species diffuse faster in the basal plane of γ‐TiAl than across the tetragonal axis direction. Qualitatively, the same result was obtained also from Connétable [ 102 ] who, in addition to γ‐TiAl, also studied H diffusion in hexagonal α 2 ‐Ti 3 Al and hcp Ti. Interestingly, the hexagonal structures exhibit faster diffusion along the hexagonal axis rather than in the basal plane.…”
Section: Materials Propertiessupporting
confidence: 82%
See 2 more Smart Citations
“…They could show that all these species diffuse faster in the basal plane of γ‐TiAl than across the tetragonal axis direction. Qualitatively, the same result was obtained also from Connétable [ 102 ] who, in addition to γ‐TiAl, also studied H diffusion in hexagonal α 2 ‐Ti 3 Al and hcp Ti. Interestingly, the hexagonal structures exhibit faster diffusion along the hexagonal axis rather than in the basal plane.…”
Section: Materials Propertiessupporting
confidence: 82%
“…All those results were shown qualitatively and also quantitatively to agree with experiments. [ 101,102 ] Zhao et al [ 103 ] showed that Nb increases migration barriers for bulk diffusion of O in γ‐TiAl and, hence, Nb improves poor oxidation resistance of the γ phase. For a comprehensive review on diffusion in the Ti−Al system, the reader is referred to publications of Mishin et al [ 104 ] or a more recent modeling‐based review of Xing et al [ 105 ]…”
Section: Materials Propertiesmentioning
confidence: 99%
See 1 more Smart Citation